Anti-ultraviolet, corrosion-resistant, low-temperature-resistant and anti-freezing geotextile material composition
By combining macromolecular anchors with small molecule functional additives, the dynamic response of functional additives is achieved, resolving the contradiction between migration and durability in existing technologies, and ensuring the material's stable performance during long-term service and adaptability to complex environmental changes.
Patent Information
- Application Number
- CN202511621733.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-07
- Publication Date
- 2025-12-05
- Estimated Expiration
- 2045-11-07
AI Technical Summary
In the existing technology, there is an inherent contradiction between the migration and durability of functional additives, which makes it difficult to guarantee the long-term service performance of materials. Furthermore, existing improvement solutions face problems such as reduced functional efficiency, high cost, complex processes, and performance degradation.
The composition of macromolecular anchor solids and small molecule functional additives is used. The functional additives are bound by non-covalent bonds and broken under specific chemical stimuli to achieve dynamic response. The amphiphilic macromolecules are enriched on the material surface to form a gradient structure, which ensures the stability of the material's performance during long-term service.
This method achieves long-term fixation and effective utilization of functional additives, ensuring stable material performance during long-term service. It can dynamically respond to changes in the external environment, avoiding performance degradation caused by physical loss in traditional methods, and does not damage the original properties of the material.
Smart Images

Figure CN121064564A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a kind of anti-UV, corrosion-resistant and low-temperature resistant anti-freezing geotextile material composition, belongs to the technical field of polymer compound composition. BACKGROUND
[0002] In the field of polymer material engineering, by the way of melt blending, phenolic antioxidant, hindered amine light stabilizer or ultraviolet absorber small molecule functional additives are uniformly dispersed in polypropylene or polyethylene polyolefin matrix, which is a common technical way to improve the ability of materials to resist light, oxygen, heat and other environmental factors; This method is widely used because these functional small molecules must have the ability to migrate in the polymer matrix to a certain extent to reach the material surface or the degradation reaction point, and then capture free radicals or absorb harmful light, the function is directly related to the movement ability of its molecular level.
[0003] However, for geotechnical materials that need to serve in harsh environments for a long time, the molecular migration characteristics that functional additives rely on to function are also the fundamental reason for their physical loss over a long period of time and ultimately leading to the attenuation of material protection performance. This thermodynamically driven molecular diffusion makes these small molecules that are not firmly connected to the polymer backbone continue to be lost through volatilization, migration to the material surface and then being washed away by rain or extracted by the contacting fluid. The direct consequence of this process is the attenuation of material protection ability. This process is slow, continuous and does not produce obvious external characteristics before material failure, resulting in that the long-term reliability of the material becomes a probabilistic speculation rather than a deterministic engineering guarantee.
[0004] To delay the loss of functional additives, the industry's technical improvement ideas mainly focus on two directions, one is to increase the molecular weight of the additive to reduce its migration rate, the second is to connect the additive to the polymer main chain in the form of covalent bond through chemical grafting, however, the former is still adjusting within the framework of migration-loss, and the fact that the functional component will eventually be exhausted has not changed, and too large molecular weight sometimes limits its efficiency in function; The latter, although it achieves permanent fixation, the complex grafting reaction not only significantly increases the production cost, but also the side reactions or catalyst residues in the process may have a negative impact on the mechanical properties and processing properties of the base material, limiting its wide application in the cost-sensitive and high-performance-consistency-demanding geotextile field. Specifically, the existing technology mainly has the following deficiencies: 1. The correlation between functionality and durability, that is, the effectiveness of functional additives depends on their migration ability, and this migration ability is the reason for their long-term loss, which is mutually restricted in the existing physical blending system; 2. The uncertainty of material life assessment, that is, the consumption rate of functional additives is closely coupled with the complex and variable factors of the service environment, making it difficult to have reliable evaluation basis for the real performance evolution of the material on the scale of decades; 3. The practical limitations of existing improvement schemes, that is, whether to simply increase the molecular weight or to use chemical grafting, they respectively face the constraints of reduced functional efficiency or high cost, complex process, and damaged performance, making it difficult to provide a solution that takes into account long-term effectiveness, economy and high performance. Therefore, how to build a new type of polymer composition system in which the functional additive can be fixed in the polymer matrix for a long time to avoid physical loss, and can effectively exert its chemical activity when needed, so as to give the polyolefin material a stable protection capability throughout its entire design life in an economical and non-damaging way to the original performance of the material, has become the technical problem to be solved by the present application. SUMMARY
[0005] The present application provides an anti-ultraviolet, corrosion-resistant and low-temperature-resistant geotextile material composition, which mainly aims to solve the problem of internal contradiction between the migration and durability of functional additives in the prior art, which leads to difficulty in ensuring the long-term service performance of the material.
[0006] To achieve the above-mentioned purpose, the present application provides an anti-ultraviolet, corrosion-resistant and low-temperature-resistant geotextile material composition, which comprises: 90 parts by weight to 98.9 parts by weight of a polypropylene matrix polymer; 0.1 parts by weight to 5 parts by weight of a small molecule functional additive, the small molecule functional additive comprising at least one of a hindered amine light stabilizer and a phenolic antioxidant; 1 to 5 parts by weight of a macromolecular anchor; the macromolecular anchor comprises a polyolefin anchoring segment chemically compatible with the polypropylene matrix polymer, having a number average molecular weight in the range of 3000 to 20000 Daltons, and a polar core; the polar core has attached thereto a plurality of recognition sites, the ratio of the molar equivalent of the recognition sites to the molar equivalent of the functional groups of the small molecule functional additive being in the range of 0.6 to 1.5; the recognition sites are attached to the polar core through a sacrificial linker, the chemical structure of the sacrificial linker being designed to stably bind the small molecule functional additive through non-covalent bonds under normal operating conditions, and to selectively break upon exposure to peroxyl radicals as a pre-determined chemical stimulus, thereby releasing the small molecule functional additive from the macromolecular anchor.
[0007] Preferably, the polar core of the macromolecular anchor comprises at least one of the functional groups selected from the group consisting of urea, uretone and triazine groups; and, the non-covalent bond formed between the recognition sites and the small molecule functional additive is a hydrogen bond, one or more combinations of stacking and dipole-dipole interactions.
[0008] Preferably, the sacrificial linker comprises a first type of sacrificial linker having a first free radical responsive breakage threshold, and a second type of sacrificial linker having a second free radical responsive breakage threshold, wherein the first free radical responsive breakage threshold is lower than the second free radical responsive breakage threshold, such that only the first type of sacrificial linker breaks when the concentration of peroxyl radicals is in a first concentration interval, and the second type of sacrificial linker breaks when the concentration of peroxyl radicals is in a second concentration interval higher than the first concentration interval.
[0009] Preferably, the molar ratio of the first type of sacrificial linker to the second type of sacrificial linker on the macromolecular anchor is in the range of 0.1 to 10. satisfies the following relationship: wherein, is the molar amount of the first type of sacrificial linker, is the molar amount of the second type of sacrificial linker, the molar ratio is set such that the amount of small molecule functional additive released by breakage of the first type of sacrificial linker is sufficient to neutralize a low-intensity, sustained oxidative attack on the composition, while reserving the small molecule functional additive immobilized by the second type of sacrificial linker as a reserve to respond to a high-intensity, acute oxidative attack.
[0010] Preferably, the chemical structure of the first type of sacrificial linker comprises a peroxide bond or a tertiary amine structure highly sensitive to oxidative stress; the chemical structure of the second type of sacrificial linker comprises a sulfide bond or a hindered phenol structure.
[0011] Preferably, the composition further comprises a heat-sensitive crystallization shield having a melting point in the range of 75 to 95°C and capable of forming a reversible crystallization shield around the first type of sacrificial linker at a temperature below the melting point, the shield inhibiting thermal degradation of the first type of sacrificial linker in the absence of peroxide radicals.
[0012] Preferably, the macromolecular anchoring body is an amphiphilic macromolecule, and the macromolecular anchoring body has a concentration gradient distribution in the composition, the concentration of the macromolecular anchoring body at the surface of the composition being higher than the concentration of the macromolecular anchoring body in the interior of the composition, the concentration gradient distribution causing the water contact angle of the surface of the composition to be smaller than the water contact angle of the interior of the composition after the composition is formed.
[0013] Preferably, the concentration of the macromolecular anchoring body at the surface of the composition, as measured by the atomic fraction of nitrogen at the surface by X-ray photoelectron spectroscopy, is 1.5 to 5 times the atomic fraction of nitrogen in the interior of the composition.
[0014] Preferably, the polypropylene base polymer is a fiber-grade isotactic polypropylene; the hindered amine light stabilizer is a hindered amine light stabilizer of type 770, the phenolic antioxidant is a phenolic antioxidant of type 1010; and the composition further comprises an ultraviolet absorber, the ultraviolet absorber being an ultraviolet absorber of type UV-531.
[0015] Preferably, the content of the macromolecular anchoring body in the composition is in the range of 1.5 to 3.5 parts by weight.
[0016] Compared with the prior art, the present application has the following beneficial effects: 1. The macromolecular anchoring body in the composition has a compatible segment that physically entangles in the melt to establish stable spatial sites in the base polymer network; at the same time, its recognition site is combined with the small-molecule functional additive through a non-covalent bond, and this structure constrains the macroscopic migration path of the additive while preserving its local activity for function, changing the long-standing technical approach in the industry that relies on the free migration of functional additives in the base polymer to function, so that the long-term performance stability of the material is no longer directly subject to the physical loss rate of the functional additives.
[0017] 2. A sacrificial linker sensitive to a specific chemical stimulus is provided between the recognition site of the macromolecular anchoring body and the small-molecule functional additive, the linker maintains stable connection under normal conditions, but selectively breaks down when a super-threshold chemical stimulus is generated in a local area due to external factors, this process converts the functional additive, which was originally in a fixed state, into a freely migratable state, enabling it to quickly replenish from the unaffected areas of the material to the attacked areas, and the protective mode of the material thus changes from a homogeneous, static overall protection to a dynamic response mode that can actively and on-demand deploy functional components according to local environmental changes.
[0018] 3、The present application, on this basis, in the sacrificial link base system, at least two kinds of link base structure with different response threshold to the same chemical stimulus are arranged in parallel, when the external stimulus intensity is at a lower level, only the link base with low threshold value is broken, and the appropriate functional additive is released to cope with the current situation; when the stimulus intensity exceeds a higher threshold value, the link base with high threshold value is broken, and the remaining functional additive is released. This configuration changes the dynamic response behavior of the material from a single trigger response to a defense mechanism that can identify the intensity of the external stimulus and respond quantitatively accordingly, thereby avoiding the premature depletion of the entire emergency capability for coping with extreme conditions when coping with low-intensity persistent attacks.
[0019] 4、The amphiphilic structure of the macromolecular anchoring body itself will migrate to the surface of the melt and solidify under the influence of the shear field or temperature gradient during the processing of the composition through melt spinning or calendering, making the polar core face the outer surface of the material. This process naturally forms a gradient structure with hydrophobic interior and polar group-rich surface layer in the formed material without any additional surface treatment steps, which unifies the durability of the material body and the interfacial functionality of the material surface, which are usually mutually contradictory performance requirements, through the same core component in the same processing flow. BRIEF DESCRIPTION OF DRAWINGS
[0020] Figure 1 Flow chart of the dynamic response mechanism of the composition of the present application; Figure 2 Relationship curve between the content of the macromolecular anchoring body and the key performance indicators of the material of the present application; Figure 3 Microscopic action mechanism diagram of the graded release of the functional additive of the present application.
[0021] Figure 4 Fourier transform infrared spectroscopy (FTIR) spectrum of the macromolecular anchoring body of the present application; Figure 5 Gel permeation chromatography (GPC) test curve of the macromolecular anchoring body of the present application. DETAILED DESCRIPTION
[0022] In order to make the purpose technical solutions and advantages of the present application clearer, the technical solutions of the present application will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0023] The embodiment of the present application provides a kind of geotextile material composition of anti-ultraviolet, corrosion-resistant and low temperature resistant freeze-proof, it includes polypropylene matrix polymer, small molecule functional additive and macromolecular anchoring body, the macromolecular anchoring body is used to fix small molecule functional additive and regulate its responsive release;In the seepage prevention engineering for large water conservancy facilities or solid waste landfill, geotextile material needs to maintain its structural and performance stability for a long time, in the prior art, to improve the durability of material, anti-aging additive is added, which depends on the molecular migration ability in polymer matrix, but this migration ability is also the main reason that causes the loss of additive due to volatilization or flushing in long-term service, and finally causes the performance degradation of material;To solve this problem, the macromolecular anchoring body in the composition of the present application, its structure includes a polyolefin anchoring segment compatible with matrix polymer, in the preparation process using twin-screw extruder for melt blending, the number average molecular weight of the anchoring segment is controlled in the range of 3000 Dalton to 20000 Dalton, the setting of this molecular weight range is based on that if the molecular weight is less than 3000 Dalton, the segment length is insufficient to form stable physical entanglement in polypropylene melt, and if the molecular weight is higher than 20000 Dalton, the melt viscosity may be too high to affect the processing fluidity of the composition, therefore, the molecular weight range is determined after technical trade-off between anchoring stability and composition processability, in this molecular weight range, the anchoring segment can form effective physical entanglement in polypropylene matrix network, so as to fix the macromolecular anchoring body in material matrix; The polar core is connected with multiple recognition sites, to ensure that the fixed functional additive can still play its chemical activity, the recognition sites and small molecule functional additive, such as 770 type hindered amine light stabilizer or 1010 type phenolic antioxidant containing active group, are combined by hydrogen bond,
[0024] In a specific embodiment, the small molecule functional additive can further comprise a UV absorber to absorb high-energy UV light and convert it into harmless heat energy, thereby reducing the generation of photo-induced free radicals from the source. The UV absorber can be selected as a UV-531 type UV absorber, which contains a hydroxyl functional group in its chemical structure, capable of forming hydrogen bonds or other non-covalent bonds with the polar groups of the recognition sites on the macromolecular anchoring body. Therefore, the UV absorber can also be fixed in the polypropylene matrix by the aforementioned anchoring method to avoid physical loss due to migration. When the UV absorber coexists with the hindered amine light stabilizer and phenolic antioxidant in the anchoring system of the present application, the three together form a multi-level synergistic protection system. The UV absorber performs the first level of energy absorption, and the hindered amine light stabilizer and phenolic antioxidant perform the second level of chemical quenching on any free radicals that are unable to be stopped, thereby improving the overall long-term photo-thermal stability of the composition. In the case of acute degradation of geotextile materials in the presence of local strong oxidizing chemicals, the aforementioned static fixation system may not respond quickly enough to cause local protection failure. To address this situation, the present application provides a sacrificial linking group between the recognition site and the polar core. The chemical structure of the sacrificial linking group, such as a specific sulfide bond or tertiary amine structure, remains stable under normal conditions to maintain the fixation of the small molecule functional additive. However, when exposed to high concentrations of peroxide radicals as a pre-set chemical stimulus, the chemical bond will undergo selective oxidative cleavage. This process allows the small molecule functional additive to be converted into a freely migratable state in the attacked local area and quickly diffuse from the surrounding undamaged material area to the area, thereby neutralizing the high concentration of active species.
[0025] Meanwhile, considering the difference in the intensity of oxidative attack in actual working conditions, to avoid premature consumption of all emergency protection capabilities when dealing with low and medium intensity attacks, the sacrificial linking group system can further be configured to contain at least two types of linking group structures with different response cleavage thresholds. The first type of sacrificial linking group uses a chemical structure such as a peroxide bond or a tertiary amine highly sensitive to oxidative stress, which requires a lower concentration of free radicals to break, to deal with low-intensity continuous attacks. The second type of sacrificial linking group uses a structure with higher chemical stability, such as a sulfide bond or a hindered phenol, which requires a higher concentration of free radicals to break, to deal with high-intensity acute attacks. The molar ratio of the two types of linking groups on the macromolecular anchoring body can be set within a specific range, for example wherein is the molar amount of the first type of sacrificial linking group, The ratio is set so that when the composition encounters a low-intensity persistent oxidative attack, the amount of functional additive released by the first type of sacrificial linking group is sufficient to cope with the attack, while the functional additive fixed by the second type of sacrificial linking group remains as a reserve to cope with a high-intensity acute oxidative attack; it should be noted that in order to ensure the stability of the first type of sacrificial linking group which is highly sensitive to oxidative stress during long-term thermal aging, the composition can also contain a heat-sensitive crystallization shielding agent, which is an oligomer with a melting point in the range of 75 to 95 degrees Celsius, which is higher than the maximum conventional service temperature of the geotextile and lower than its processing temperature. When the melting point is lower than the melting point, the shielding agent molecules form a reversible crystalline shielding layer around the polar core of the macromolecular anchor, which can reduce the thermal degradation rate of the first type of sacrificial linking group in the absence of peroxide radicals, thereby ensuring the long-term effectiveness of the hierarchical response mechanism; in applications where the geotextile needs to be laminated with other materials, the surface properties are also key parameters. The macromolecular anchor can be used as an amphiphilic macromolecule. During the melt processing of the composition, the shearing field or temperature gradient is applied to induce its migration to the surface of the melt. After cooling and solidification, the macromolecular anchor has a concentration gradient distribution in the composition, and the concentration of the macromolecular anchor on the surface of the composition is higher than that in the interior of the composition. The concentration gradient distribution makes the water contact angle of the surface of the composition smaller than that of the interior of the composition after forming, thereby improving the functionality of the material surface without additional surface treatment processes.
[0026] Example 1: In a high-standard hazardous chemical landfill project designed to serve for more than 100 years, the polypropylene geotextile used in the impermeable system needs to withstand long-term strong ultraviolet radiation, annual temperature difference cycles exceeding 60 degrees Celsius, and the continuous action of low-concentration oxidative substances generated by the decomposition of residual organic matter in the leachate; for conventional modified geotextile materials, durability evaluation relies on a statistical model based on the migration and loss rate of functional additives, which cannot provide a deterministic performance guarantee for the 100-year service life of the project; under these working conditions, the geotextile prepared by the composition of the foregoing specific embodiments has macromolecular anchors inside, which are physically entangled with the polypropylene matrix through the polyolefin anchor segment, fixing themselves and small-molecule functional additives combined by non-covalent bonds in the material network. This structure blocks the migration path of the functional additive, avoiding the degradation of the protective performance caused by physical loss in long-term service, and at the same time, since the functional additive is combined by non-covalent bonds with moderate bond energy, the molecular activity of the free radical capture is retained, thereby solving the conflict between the migration and persistence of traditional additives.
[0027] When a small portion of waste liquid containing high concentration of peroxide leaked due to operational error during the landfill operation, and directly contacted the surface of the geotextile, the material in the local area was attacked by ultra-high concentration of peroxide radicals; in this area, the sacrificial linker contained in the macromolecular anchoring body structure selectively broke its chemical bond to the concentration of free radicals, this process triggered the local release of small molecule functional additives originally anchored, these released functional additives, driven by the concentration gradient, quickly supplemented from the surrounding unaffected material area to the attacked core area, forming a local high concentration protective layer, effectively neutralizing the peroxide radicals, this process uses the peroxide radicals as a degradation trigger, and converts it into a regulatory signal that triggers a transient increase in local protection capacity; after the local chemical attack event is handled, the incident point loses its emergency response ability due to the consumption of functional additives, but the surrounding vast area of geotextile material, which has not experienced ultra-threshold chemical stimulation, still has its internal functional additive reserves stably anchored by the macromolecular anchoring body, the long-term anti-ultraviolet and anti-thermal oxidative aging performance benchmark of the entire impermeable system is not affected, and the predictability of the overall performance evolution path of the material is maintained.
[0028] Example 2: To objectively verify the performance stability of the composition of the present application under long-term photo-thermal aging conditions, and to define the content range of the key component macromolecular anchoring body, an accelerated aging comparative test was conducted. Seven groups of samples were prepared, and the fiber-grade isotactic polypropylene was used as the base polymer, and the reference melt mass flow rate of the base polymer was 3.0 g / 10 min under the condition of 230°C and 2.16 kg load; the mixture of 770 type hindered amine light stabilizer and 1010 type phenolic antioxidant was used as the small molecule functional additive, and the macromolecular anchoring body was prepared by reacting maleic anhydride grafted polypropylene (PP-g-MAH) with a number average molecular weight Mn≈8500 g / mol and a grafting rate of 1.0% with N,N-dimethyl-1,3-propanediamine as the first type of sacrificial linker precursor monomer and 4,7,10-trioxa-1,13-tridecanediamine (molar ratio Rlink≈0.3) as the second type of sacrificial linker precursor monomer, and then reacted with toluene-2,4-diisocyanate (TDI) to form a polar core. The number average molecular weight of the macromolecular anchoring body was 11500 g / mol; a double-screw extruder was used for blending and extrusion at 220°C, and standard tensile sample strips were prepared by tabletting. The formulations of each group were as follows: control group 1 contained 98 parts of polypropylene base and 2 parts of small molecule functional additive; control group 2 contained 97 parts of polypropylene base and 3 parts of macromolecular anchoring body, without small molecule functional additive; control group 3 contained 0.5 parts of macromolecular anchoring body; control group 4 contained 6.0 parts of macromolecular anchoring body; test group 1 contained 1.5 parts of macromolecular anchoring body; test group 2 contained 3.0 parts of macromolecular anchoring body; test group 3 contained 4.5 parts of macromolecular anchoring body. Except for control groups 1 and 2, the total amount of small molecule functional additive was kept constant, and the polypropylene base content was adjusted so that the total of each group was 100 parts; all the tensile sample strips of all groups were placed in the same xenon lamp aging test box, and accelerated aging was carried out according to GB / T16422.2 standard, the test conditions were set as follows: the irradiance at 340 nm wavelength was , the blackboard temperature was 65 , and the humidity cycle was implemented. At 0h, 500h, 1000h, 1500h and 2000h of the aging process, samples were taken from each group for tensile strength test, and the tensile strength retention rate relative to the initial strength of each group was calculated.
[0029] The test data show that the tensile strength retention of each sample group decreases to different degrees with the increase of aging time. The strength retention of the control group 1 without macromolecular anchoring body decreases rapidly and is reduced to 50.1% of the initial value after 1000h. The strength retention of the control group 2 without small molecule functional additive decreases most seriously and is only 28.6% after 1000h. The performance of the control group 3 with less than 1 part of macromolecular anchoring body decreases more slowly than the control group 1, but the strength retention is also reduced to 61.5% after 1000h. The initial strength of the control group 4 with more than 5 parts of macromolecular anchoring body decreases slightly, and the 90.3% strength retention after 1000h does not show further advantages compared with the test groups. The test groups 1 to 3 with 1.5 to 4.5 parts of macromolecular anchoring body all show high strength retention, and the values are maintained above 92% after 1000h. For specific data, refer to Table 1.
[0030] Table 1: Tensile strength retention of each sample group at different aging times.
[0031] The analysis of the data shown in Table 1 shows that the rapid performance decline of the control group 1 is due to the physical loss of the small molecule functional additive not fixed under the light and heat conditions. The comparison of the performance of the control group 1, the control group 2 and each test group shows that the combination of the macromolecular anchoring body and the small molecule functional additive has a synergistic effect on obtaining long-term stability. The data of the control group 3 shows that when the content of the macromolecular anchoring body is less than 1 part, the anchoring network formed in the matrix is not enough to effectively fix all the additive molecules. The data of the control group 4 shows that when the content of the macromolecular anchoring body is more than 5 parts, there is no better performance, and the slight decrease of the initial strength may be related to the dispersibility of the excess polar component in the non-polar matrix. According to the test results, the content of the macromolecular anchoring body in the range of 1 to 5 parts is a technical selection for the composition of the present application to obtain long-term light stability.
[0032] Example 3: This example combines Figures 1 to 5 to explain a geotextile material composition with anti-ultraviolet, corrosion resistance and low-temperature frost resistance, like Figure 1As shown in the diagram, the process begins with a judgment of the effects of the external environment. Under normal operating conditions, i.e., when the judgment result for whether an over-threshold chemical stimulus is negative, the system enters a static protection mode. In this mode, the sacrificial linker remains stable, and the functional additive is firmly anchored, thereby achieving long-term and durable protection. However, when encountering an acute attack, i.e., when the judgment result is positive, the system enters a dynamic response mode. This mode first determines the attack intensity. For low-intensity continuous attacks, the first type of sacrificial linker is broken, while for high-intensity acute attacks, the second type of sacrificial linker is broken. Both paths lead to the on-demand release of the functional additive, causing it to change from a fixed state to a free-migrating state.
[0033] like Figure 2 As shown, the horizontal axis represents the content of macromolecular anchor solids in parts by weight, the left vertical axis represents the strength retention rate after 2000 hours of aging in percentage (%), and the right vertical axis represents the puncture resistance in Newtons (N). The three curves in the figure correspond to the three performance indicators of strength retention rate, puncture resistance, and melt flow rate after 2000 hours, respectively. The curves show that as the content of macromolecular anchor solids increases from 1.5 parts by weight to 3.5 parts by weight, the strength retention rate of the material after 2000 hours shows a trend of first increasing and then stabilizing, reaching a peak plateau when the content is about 2.5 to 3.0 parts by weight. The puncture resistance also reaches its maximum value near this range, while the melt flow rate decreases monotonically with the increase of content.
[0034] like Figure 3 As shown, the diagram consists of three state diagrams. State (I) shows the stable anchoring state under normal operating conditions, where the functional additives HALS and AO are firmly bonded to the polar core through linking groups. State (II) shows that under low-intensity oxidation (low concentration of RO·), only the first type of linking group, which is more sensitive to oxidative stress, breaks, resulting in the release of the functional additive HALS, while AO remains in the anchoring state. State (III) shows that under high-intensity oxidation (high concentration of RO·), both the first and second type of linking groups break.
[0035] like Figure 4 As shown, this figure displays its Fourier transform infrared spectrum (... The spectrum, with the vertical axis representing transmittance ( The horizontal axis represents the wave number (). The figure clearly shows several characteristic absorption peaks used to confirm the chemical structure, including Stretching (imide) Stretching (imide) Stretching (urea group), aromatic ring skeleton vibration, Stretching (alkylpropylene) and Stretching (urea group); such asFigure 5 The figure shows a gel permeation chromatogram of the macromolecular anchor ) with the ordinate representing detector response (AU) and the abscissa representing elution time (min).
[0036] Example 4: In the application of geotextile in agricultural irrigation and drainage channels, the material not only needs to withstand continuous sunlight, but also needs to cope with long-term slow oxidation of low-concentration residual herbicides in the channel water and short-term impact of high-concentration oxidizing pesticides due to upstream leakage, so the proportions of different response rate protection components in the material need to be matched to adapt to this composite aging environment; to determine the appropriate molar ratio , a series of test samples were first prepared, each sample group used fiber-grade isotactic polypropylene with a melt mass-flow rate (230°C, 2.16kg load) of 3.0g / 10min as the base polymer, and used 770 hindered amine light stabilizer and 1010 phenolic antioxidant as small molecule functional additives, and the total content of macromolecular anchor was 3.0 parts by weight; the macromolecular anchor itself was prepared by reacting maleic anhydride grafted polypropylene (PP-g-MAH) with N,N-dimethyl-1,3-propanediamine (first type of sacrificial linker precursor monomer), 4,7,10-trioxa-1,13-tridecanediamine (second type of sacrificial linker precursor monomer), and toluene-2,4-diisocyanate (TDI); by adjusting the molar ratio of the two corresponding active monomers in the step of synthesizing the macromolecular anchor, five sample groups with molar ratios of the first type of sacrificial linker to the second type of sacrificial linker of 0.1, 0.2, 0.3, 0.4 and 0.5 were prepared, and were labeled as sample groups R0.1 to R0.5; then, all sample groups were subjected to two-stage sequential aging test, in the first stage, the sample groups were soaked in 0.01mol / L hydrogen peroxide solution and treated at 60 for 500 hours to simulate a long-term low-intensity oxidation environment, after the end of this stage, the remaining proportion of functional additives still fixed by the second type of sacrificial linker in each sample group was quantitatively detected by chemical analysis method; in the second stage, the sample groups that completed the first stage test were immediately immersed in 1.0mol / L hydrogen peroxide solution and treated at 60 for 24 hours to simulate high-intensity acute chemical impact, after the test was completed, the tensile strength retention rate of each sample group was measured.
[0037] Experimental data show that after completing the first stage of testing, sample R0.1 had the highest remaining proportion of functional additives fixed by the second type of sacrificial linking group, at 95%, while the remaining proportion of this functional additive in sample R0.5 was less than 50%. After completing the second stage of testing, sample R0.1, due to cumulative damage to the polymer matrix in the first stage, had a final tensile strength retention rate of less than 40%. Sample R0.5, due to excessive consumption of functional additives fixed by the second type of sacrificial linking group in the first stage, had a final strength retention rate of approximately 60%. Samples R0.2 and R0.3, however, had a remaining proportion of functional additives fixed by the second type of sacrificial linking group higher than 80% after the first stage, and a final tensile strength retention rate higher than 85% after the second stage of testing. The results of this calibration method indicate that, for this application environment, adjusting the molar ratio... Setting it within the range of 0.2 to 0.3 is a technical choice that allows the material to balance long-term continuous protection with short-term emergency protection.
[0038] Example 5: In the preparation of a geotextile, the application scenario requires the material surface to be hydrophilic to facilitate adhesion to cement-based materials, while its built-in responsive protection system must be able to withstand the high-temperature environment during storage. The preparation process uses the following basic formulation: fiber-grade isotactic polypropylene as the matrix polymer with a baseline melt flow rate (230°C, 2.16kg load) of 3.0g / 10min, and type 770 hindered amine light stabilizer and type 1010 phenolic antioxidant as small components. The product contains a functional additive and 3.0 parts by weight of a macromolecular anchor solid. This macromolecular anchor solid (number-average molecular weight 11500 g / mol, molar ratio Rlink≈0.3) is prepared by reacting maleic anhydride-grafted polypropylene (PP-g-MAH) with N,N-dimethyl-1,3-propanediamine, 4,7,10-trioxa-1,13-tetanediamine, and toluene-2,4-diisocyanate (TDI). Based on this basic formulation, an additional 1.5 parts by weight of a substance with a melting point of 85°C is added. Polycaprolactone oligomers were used as heat-sensitive crystallization shielding agents. After melt blending, the materials were calendered using a three-roll calendering device. The surface temperature of the calendering roller in contact with the upper surface of the material was set to 140°C. The surface temperature of the calendering roller that contacts the lower surface is set to 155°C. The material passes through the roller gap at a processing linear speed of 10 m / min.
[0039] The performance of the geotextile samples prepared by the above process was confirmed. The water contact angle of its upper surface was measured using a contact angle measuring instrument. The water contact angle of the lower surface is This data indicates that, under the temperature gradient of the calender roll, the amphiphilic macromolecular anchoring body in the composition has migrated and enriched to the upper surface with lower temperature; then, to verify the effect of the heat-sensitive crystallization shielding agent, the sample was placed in an 80 environment for 720 hours of heat aging, and after the aging treatment, the sample was subjected to low-intensity oxidation testing according to the first-stage test method. The test results showed that the remaining proportion of the functional additive fixed by the second type of sacrificial linking group in the sample of the present embodiment was higher than 90%, while the remaining proportion of this part of the functional additive in the comparative sample was lower than 60%.
[0040] Example 6: In determining the geotextile formulation for a specific coastal protection project, the content of the macromolecular anchoring body needs to be calibrated to balance the long-term durability of the material and the processing fluidity. For this purpose, five groups of samples were prepared, each using a fiber-grade isotactic polypropylene with a reference melt mass flow rate (230°C, 2.16kg load) of 3.0g / 10min as the base polymer, and using a 770 type hindered amine light stabilizer and a 1010 type phenolic antioxidant as the small molecule functional additive. The macromolecular anchoring body used (number average molecular weight 11500g / mol, molar ratio Rlink≈0.3) was prepared by reacting maleic anhydride grafted polypropylene (PP-g-MAH) with N,N-dimethyl-1,3-propanediamine, 4,7,10-trioxa-1,13-tridecanediamine and toluene-2,4-diisocyanate (TDI). The weight content of the macromolecular anchoring body in the five groups of samples was 1.5 parts, 2.0 parts, 2.5 parts, 3.0 parts and 3.5 parts, respectively, with the remaining components remaining unchanged. The five groups of samples were subjected to performance testing, including the tensile strength retention rate after aging for 2000 hours, the initial puncture resistance and the melt mass flow rate (MFR) under a load of 230 , 2.16kg. The test results showed that when the content of the macromolecular anchoring body was 2.5 parts, the tensile strength retention rate of the sample after aging was not significantly different from that of the samples with a content of 3.0 parts and 3.5 parts, but the melt mass flow rate was 3.8g / 10min, higher than the latter two, indicating that it had better processing fluidity, and its puncture resistance reached a maximum value near this content point, so 2.5 parts by weight was determined as the preferred addition amount under this application condition.
[0041] To cope with the difference of melt flowability of different batches of polypropylene raw materials, a set of pre-production process parameter fine-tuning procedures was established. The procedures clearly stated that for each new batch of polypropylene raw material, the melt mass flow rate under standard conditions was first determined and compared with the benchmark value of 3.0 g / 10 min. If the deviation between the measured value and the benchmark value was within ±5%, the production process parameters remained unchanged. If the measured value was 5% higher than the benchmark value, the screw rotation speed of the twin-screw extruder was increased by 3% accordingly to increase the mixing effect. If the measured value was 5% lower than the benchmark value, the set temperature of the first heating zone of the extruder was increased by 5 to reduce the melt viscosity.
[0042] Example 7: In a 500 mL four-necked flask equipped with mechanical stirring, thermometer and nitrogen inlet tube, 200 mL of anhydrous xylene was added as a solvent, and the temperature was raised to 120 °C under nitrogen protection, 50 g of maleic anhydride grafted polypropylene (PP-g-MAH, number average molecular weight Mn ≈ 8500 g / mol, grafting rate 1.0%) was added and stirred until completely dissolved; then, 0.31 g of N, N-dimethyl-1, 3-propanediamine (as a precursor monomer of the first type of sacrificial linker) and 1.22 g of 4, 7, 10-trioxa-1, 13-tridecanediamine (as a precursor monomer of the second type of sacrificial linker, molar ratio Rlink ≈ 0.3) were dissolved in 20 mL of anhydrous xylene, and were added dropwise into the reaction system through a constant pressure dropping funnel within 30 minutes. After the addition was completed, the reaction was continued at 120 °C for 4 hours to allow the amines of the diamines to undergo ring-opening reaction with the anhydride groups of PP-g-MAH to form amido acid structures.
[0043] After the reaction was completed, the reaction system was cooled to 80 °C, 10 g of toluene-2, 4-diisocyanate (TDI) was added, and the reaction was continued for 2 hours to allow the isocyanate groups to react with the carboxyl groups of the amido acid and the remaining amino groups to form a polar core. After the reaction was completed, the product was poured into a large amount of acetone for precipitation, filtered, washed with acetone three times, and then dried in a vacuum oven at 80 °C for 24 hours to obtain a white powdery macromolecular anchor, the number average molecular weight of which was 11500 g / mol as measured by gel permeation chromatography (GPC), and the characteristic absorption peaks of imide and urea groups were confirmed by Fourier transform infrared spectroscopy (FTIR).
[0044] It is obvious to those skilled in the art that the present application is not limited to the details of the above exemplary embodiments, and the present application can be implemented in other specific forms without departing from the spirit or essential characteristics of the present application.
[0045] Finally, it should be noted that the above examples are merely intended to illustrate the technical solutions of the present application and not to limit the present application. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or equivalently replaced without departing from the spirit and scope of the present application.
Claims
1. An ultraviolet resistant, corrosion resistant and low temperature resistant anti-icing geotextile material composition, characterized by, The composition comprises: 90 to 98.9 parts by weight of a polypropylene matrix polymer; 1 to 5 parts by weight of a small-molecule functional additive, the small-molecule functional additive comprising at least one of a hindered amine light stabilizer and a phenolic antioxidant; 1 to 5 parts by weight of a macromolecular anchor, the macromolecular anchor comprising a polyolefin anchor segment chemically compatible with the polypropylene matrix polymer and having a number average molecular weight in the range of 3000 to 20000 Daltons, and a polar core; the polar core having a plurality of recognition sites attached thereto, the ratio of the molar equivalent of the recognition sites to the molar equivalent of the reactive groups of the small-molecule functional additive being in the range of 0.6 to 1.5; the recognition sites being attached to the polar core through a sacrificial linker, the sacrificial linker being designed to stably bind the small-molecule functional additive through non-covalent bonds under normal operating conditions and to selectively break upon exposure to peroxide radicals as a pre-determined chemical stimulus, thereby releasing the small-molecule functional additive from the macromolecular anchor.
2. The UV resistant, corrosion resistant and low temperature resistant anti-freezing geotextile material composition according to claim 1, characterized in that, The polar core of the macromolecular anchor comprises at least one of the functional groups consisting of urea, uretone and triazine groups; and the non-covalent bond formed between the recognition site and the small molecule functional additive is a hydrogen bond, one or more combinations of stacking and dipole-dipole interactions.
3. The UV resistant, corrosion resistant and low temperature resistant anti-freezing geotextile material composition according to claim 1, characterized in that, The sacrificial linker comprises a first type of sacrificial linker having a first radical-responsive breaking threshold, and a second type of sacrificial linker having a second radical-responsive breaking threshold, wherein the first radical-responsive breaking threshold is lower than the second radical-responsive breaking threshold, such that only the first type of sacrificial linker breaks when the concentration of peroxide radicals is in a first concentration interval, and the second type of sacrificial linker breaks when the concentration of peroxide radicals is in a second concentration interval higher than the first concentration interval.
4. The UV resistant, corrosion resistant and low temperature resistant anti-icing geotextile material composition according to claim 3, characterized in that, molar ratio of the first type of sacrificial linking group to the second type of sacrificial linking group on the macromolecular anchor satisfies the following relationship: wherein, is the molar amount of the first type of sacrificial linking group, is the molar amount of the second type of sacrificial linking group, the molar ratio is set such that the amount of small molecule functional additive released by the cleavage of the first type of sacrificial linking group is sufficient to neutralize a low severity, sustained oxidative attack on the composition while preserving the small molecule functional additive immobilized by the second type of sacrificial linking group as a reserve to respond to a high severity, acute oxidative attack.
5. The UV resistant, corrosion resistant and low temperature resistant anti-icing geotextile material composition according to claim 3, characterized in that, The chemical structure of the first type of sacrificial linker comprises a peroxide bond or a tertiary amine structure highly sensitive to oxidative stress; the chemical structure of the second type of sacrificial linker comprises a sulfide bond or a hindered phenol structure.
6. The UV resistant, corrosion resistant and low temperature resistant anti-icing geotextile material composition according to claim 3, characterized in that, The composition further comprises a heat-sensitive crystallization shield having a melting point in the range of 75 to 95 degrees Celsius.
7. The UV resistant, corrosion resistant and low temperature resistant anti-icing geotextile material composition as claimed in claim 1, wherein, The macromolecular anchor is an amphiphilic macromolecule, and the macromolecular anchor exhibits a concentration gradient distribution in the composition, the concentration of the macromolecular anchor being higher at the surface of the composition than in the interior of the composition, the concentration gradient distribution causing the water contact angle of the surface of the composition to be smaller than the water contact angle of the interior of the composition after the composition is formed.
8. The UV resistant, corrosion resistant and low temperature resistant anti-icing geotextile material composition as claimed in claim 7, wherein, The concentration of the macromolecular anchor at the surface of the composition, as measured by the atomic fraction of nitrogen element at the surface by X-ray photoelectron spectroscopy, is in the range of 1.5 to 5 times the atomic fraction of nitrogen element in the interior of the composition.
9. The UV resistant, corrosion resistant and low temperature resistant anti-icing geotextile material composition as claimed in claim 1, wherein, The polypropylene matrix polymer is a fiber-grade isotactic polypropylene; the hindered amine light stabilizer is a hindered amine light stabilizer of type 770, and the phenolic antioxidant is a phenolic antioxidant of type 1010.
10. The UV resistant, corrosion resistant and low temperature resistant anti-icing geotextile material composition as claimed in claim 1, wherein, The parts by weight content of the macromolecular anchor is in the range of 1.5 to 3.5 parts.
Citation Information
Patent Citations
High-performance polypropylene composite material and preparation method thereof
CN118725458A
Weather-resistant anti-aging polypropylene material and preparation method thereof
CN120310136A
Radiation-Induced Thickening for Set-On-Command Sealant Compositions and Methods of Use
US20110048715A1
Process for Preparing High Melt Strength Polypropylene
US20200062880A1